Decreased Hyperpolarization-Activated Cyclic Nucleotide-Gated Channel 2 Activity in a Rat Model of Absence Epilepsy and the Effect of ZD7288, an Ih Inhibitor, on the Spike-and-Wave Discharges - AYDIN OMAY, BANU; ONAT, FİLİZ (KARGER, 2022)
Introduction: Hyperpolarization-activated cyclic nucleotide-gated (HCN) channel currents of Ih and absence epilepsy seizures are associated, but studies reveal differential results. Objective: In our study, we aimed to investigate the role of the HCN channels on the expression of spike-and-wave discharges (SWDs) using the Genetic Absence Epilepsy Rats from Strasbourg (GAERS) model. Methods: HCN isoform levels from isolated brains of both naive nonepileptic Wistar and GAERS groups were evaluated by enzyme-linked immunosorbent assay. ZD7288, an Ih inhibitor as well as an HCN channel antagonist, was administered intracerebroventricularly to the adult GAERS groups, and to evaluate their SWD activities, electroencephalography was recorded. The effect of ZD7288 on the cumulative total duration and number of SWDs and the mean duration of each SWD complex was evaluated. Results: The HCN2 levels in the cortex and hippocampus of the GAERS group were lower compared to the naive nonepileptic Wistar group (p < 0.05). ZD7288 increased the number of SWDs at the 20th and 120th min with the highest administered dose of 7 mu g (p < 0.05). Conclusion: The Ih inhibitor ZD7288 increased the number of SWDs in a genetic absence epilepsy rat model, although this increase may not be significant due to the inconsistent time-dependent effects. In GAERS, the cortical and hippocampal HCN2 channel levels were significantly lower compared to the control group. Further studies are needed with higher doses of ZD7288 to determine if the effects will increase drastically.
Keywords: Hyperpolarization-activated cyclic nucleotide-gated channels; Spike-and-wave discharges; ZD7288; Genetic absence epilepsy; Hippocampus; VISUAL-CORTEX; NEURONS; OSCILLATION; TERMINATION; EXPRESSION; THALAMUS; FIBERS